Paziowie krola Zygmunta - Domanska, Antonina, 1853-1917. (Wroclaw : Wydawnictwo Siedmiorog, 1997)
An historical novel for children about the pages in the court of King Zygmunt. Ages 8-12.
Keywords: Children's stories, Polish